Diseño de plan de mantenimiento preventivo para el taller de fabricación de moldes en la empresa Casald Ingeniería SAS (2024)
"Maintenance is of vital importance in the industry nowadays, due to all its significant contributions in the industrial processes, mainly in the quality and optimization of the manufacturing processes reducing the failures in the machinery and, therefore, the time out of service, preserving the assets for a longer time; all this entails economic benefits for the company. It is for this reason that the implementation of a maintenance plan executed according to the needs of the company CASALD INGENIERIAS SAS is proposed, it is established to be of preventive nature in order to preserve the machinery in optimal operating conditions reducing the most common failures in them, improving the availability and reliability in the development of their functions. The injection mold manufacturing process was selected due to the various operations involved such as cutting, milling and sanding of the molds. This process involves the main machines available in the company for the different steel transformation processes and is useful in all the company's production processes. Initially, a detailed analysis of the mold manufacturing process was carried out, as well as the maintenance techniques currently used on the machinery, which are characterized by being of a corrective nature due to the absence of a structured maintenance plan. We proceeded to verify the general information of the equipment during the time interval from June 2023 to May 2024 in order to identify the main failures and their frequency. Failure and critical component sheets were prepared in order to obtain the operation information in an accessible and accurate manner. Subsequently, we proceed to characterize the behavior of the machinery involved in the mold manufacturing process through the calculations of the proposed maintenance indicators such as maintainability, availability and reliability, creating the parameterization of the criteria according to the company's environment, being an input to continue with the development of the preventive maintenance plan. It was decided to use the Failure Mode and Effect Analysis (FMEA) methodology, which proactively covers the identification, mitigation and evaluation of potential failures in the machinery involved in the mold manufacturing process, generating solutions that help to improve the availability and reliability in the development of the equipment functions, saving time and money in the production process, and improving the quality and reliability of the equipment, thus saving time and money in the production process. By means of the analyses carried out, it was diagnosed that the Haida injector and the CNC milling machine are the most critical machines because they present more failures and the process does not have a backup machine that performs the same functions, while the HotPlast injector is the one that presents the lowest availability, justified by the long time of its corrective interventions; the arbor milling machine and the lathe present similar behavior patterns in the maintenance indicators, reflected in their total number of failures and intervention times. It is proposed to carry out a schedule of preventive maintenance activities planned for one year, based on three key activities: inspection, cleaning and lubrication of the machines. The objective is to reduce failure frequencies, optimize the production process, reduce costs associated with maintenance and improve process quality by increasing the maintenance indicators previously established. To meet these objectives in the implementation of the plan, all the information of the production process must be collected to evaluate if the actions are giving the expected results. In addition, compliance with the planned activities must be ensured, with the machine operators being fundamental to the success of the maintenance plan, complying with the assigned activities and reporting any anomaly in the operation in a timely manner. To conclude, a series of graphs are presented with the objective of continuing to evolve in maintenance activities, achieving in the future that all of the company's assets are supported by maintenance planning, progressively implementing improved activities and techniques, through the use of technological tools for measuring and detecting failures in order to advance in the development of production processes, meeting the objectives set and maintaining a more competitive position in the industry."